2020
DOI: 10.1016/j.jaim.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Punica granatum improves renal function in gentamicin-induced nephropathy in rats via attenuation of oxidative stress

Abstract: Data suggests that MPGL attenuated oxidative stress associated renal injury by preserving antioxidant enzymes, reducing lipid peroxidation and inhibiting inflammatory mediators such as TNF-α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 25 publications
4
29
0
Order By: Relevance
“…The levels of creatinine and urea in the serum of the groups that received GM and pre-treated with cinnamon and/or parsley oils were significantly declined, suggesting the protective potentials of cinnamon and parsley against kidney damage induced by GM. As mentioned before, after GM treatment, the use of compounds that possesses antioxidant effect improves renal function (Mestry et al, 2018). Serum creatinine and urea levels and the results of pathohistological analysis reflected the development of kidney impairment in GM-administered rats.…”
Section: Resultsmentioning
confidence: 63%
“…The levels of creatinine and urea in the serum of the groups that received GM and pre-treated with cinnamon and/or parsley oils were significantly declined, suggesting the protective potentials of cinnamon and parsley against kidney damage induced by GM. As mentioned before, after GM treatment, the use of compounds that possesses antioxidant effect improves renal function (Mestry et al, 2018). Serum creatinine and urea levels and the results of pathohistological analysis reflected the development of kidney impairment in GM-administered rats.…”
Section: Resultsmentioning
confidence: 63%
“…Furthermore, a previous study showed that the isoprenoid 10-hydroxyloganin had an insecticidal effect [83]. The limonoid khayanthone was detected in Punica granatum methanolic extract, which exhibited antioxidant potentiality [84]. The compounds 13R-hydroxy-9E,11Z-octadecadienoic, acid bis (2-hydroxypropyl) amine, 9-aminononanoic acid, and 10-aminodecanoic acid found in this plant, which belong to fatty acids, amino alcohols, and amino acid derivatives, were proved in the literature to have antiradical activity [85,86].…”
Section: Antioxidant Activitiesmentioning
confidence: 95%
“…The protective effect of PGPE on the creatinine and urea could be attributed to its antioxidant effect as ROS has been found to be involved in the impairment of glomerular filtration rate [ 57].…”
Section: Discussionmentioning
confidence: 99%